2022
DOI: 10.3389/ftox.2022.956885
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of microplastics on immunity

Abstract: Most disposable plastic products are degraded slowly in the natural environment and continually turned to microplastics (MPs) and nanoplastics (NPs), posing additional environmental hazards. The toxicological assessment of MPs for marine organisms and mammals has been reported. Thus, there is an urgent need to be aware of the harm of MPs to the human immune system and more studies about immunological assessments. This review focuses on how MPs are produced and how they may interact with the environment and our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 132 publications
0
22
0
3
Order By: Relevance
“…Perhaps sterile inflammation from microplastics is our closest analogy to sterile inflammation from a mutually mystified alien biology (Yang et al, 2022). It's broadly similar to other forms of sterile inflammation.…”
Section: Our Treg Cells Mightmentioning
confidence: 99%
See 4 more Smart Citations
“…Perhaps sterile inflammation from microplastics is our closest analogy to sterile inflammation from a mutually mystified alien biology (Yang et al, 2022). It's broadly similar to other forms of sterile inflammation.…”
Section: Our Treg Cells Mightmentioning
confidence: 99%
“…The reactive oxygen species, DAMP, inflammation and cell death are all detected but the other details need to be clarified. (Yang et al, 2022) First, coated microplastics (MP) shown in blue get taken up by the white blood cells (macrophages). The microplastics interfere with the mitochondria, the energy powerhouses of the cell that turn oxygen into energy.…”
Section: Our Treg Cells Mightmentioning
confidence: 99%
See 3 more Smart Citations